Morphological characterization of native mexican tomato populations (Solanum lycopersicum (L.) Mill.) (Agro Productividad, 2026)
Objective: To characterize native populations of tomato (Solanum lycopersicum (L.) Mill.) collected from different regions of Mexico in order to determine their morphological diversity and potential use in breeding.Design/methodology/approach: One hundred native tomato populations originating from 17 climatic regions in central and southern Mexico, along with two commercial hybrids, were cultivated in a completely randomized block design with two replications under greenhouse conditions. The crop was grown up to the tenth cluster, and morphological evaluation was carried out on the sixth cluster by measuring 28 variables. The statistical analysis included descriptive statistics, univariate analysis of variance, and mean comparison tests. Multivariate analyses included cluster analysis and principal component analysis.Results: In the descriptive analysis, the variables with intermediate variability were average fruit weight and number of locules. Based on fruit shape, fruits were classified into the following types: kidney, squash, irregular shapes, pear, bell, round, flattened round, saladette, and cherry. In the principal component analysis, native populations were dispersed into eight groups according to their degree of domestication, earliness, and geographic origin. In the cluster analysis, the populations were distributed into 14 groups; Group 13 was shared by populations from Puebla, Guerrero, and the commercial hybrids, indicating that they share common traits.Limitations of the study/Implications: Studies on culinary and nutritional quality in native tomato populations could be conducted to complement the information obtained.Findings/Conclusions: Fruits from native tomato populations from Mexico exhibited considerable variability. This diversity is manifested in different fruit types, sizes, and number of locules. Understanding morphological variability opens the possibility for their inclusion in genetic improvement programs.